Volatile ultrafast switching at multilevel nonvolatile states of phase change material for active flexible terahertz metadevices - Pitchappa, Prakash (2022)
Phase change materials provide unique reconfigurable properties for photonic applications that mainly arise from their exotic characteristic to reversibly switch between the amorphous and crystalline nonvolatile phases. Optical pulse based reversible switching of nonvolatile phases is exploited in various nanophotonic devices. However, large area reversible switching is extremely challenging and has hindered its translation into a technologically significant terahertz spectral domain. Here, this limitation is circumvented by exploiting the semiconducting nature of germanium antimony telluride (GST) to achieve dynamic terahertz control at picosecond timescales. It is also shown that the ultrafast response can be actively altered by changing the crystallographic phase of GST. The ease of fabrication of phase change materials allows for the realization of a variable ultrafast terahertz modulator on a flexible platform. The rich properties of phase change materials combined with the diverse functionalities of metamaterials and all-optical ultrafast control enables an ideal platform for design of efficient terahertz communication devices, terahertz neuromorphic photonics, and smart sensor systems.